Linking 1D evolutionary to 3D hydrodynamical simulations of massive stars. (1st March 2016) - Cristini, A; Meakin, C; Hirschi, R; Arnett, D; Georgy, C; Viallet, M
Abstract: Stellar evolution models of massive stars are important for many areas of astrophysics, for example nucleosynthesis yields, supernova progenitor models and understanding physics under extreme conditions. Turbulence occurs in stars primarily due to nuclear burning at different mass coordinates within the star. The understanding and correct treatment of turbulence and turbulent mixing at convective boundaries in stellar models has been studied for decades but still lacks a definitive solution. This paper presents initial results of a study on convective boundary mixing (CBM) in massive stars. The 'stiffness' of a convective boundary can be quantified using the bulk Richardson number ( ), the ratio of the potential energy for restoration of the boundary to the kinetic energy of turbulent eddies. A 'stiff' boundary ( ) will suppress CBM, whereas in the opposite case a 'soft' boundary ( ) will be more susceptible to CBM. One of the key results obtained so far is that lower convective boundaries (closer to the centre) of nuclear burning shells are 'stiffer' than the corresponding upper boundaries, implying limited CBM at lower shell boundaries. This is in agreement with 3D hydrodynamic simulations carried out by Meakin and Arnett (2007 Astrophys. J.  667 448–75 ). This result also has implications for new CBM prescriptions in massive stars as well as for nuclear burning flame front propagation in super-asymptotic giant branch stars and also the onset of novae.